Untamed - Doyle, Glennon, 1976- (The Dial Press, 2020)
"There is a voice of longing inside every woman. We strive so mightily to be good: good mothers, daughters, partners, employees, citizens, and friends. We believe all this striving will make us feel alive. Instead, it leaves us feeling weary, stuck, overwhelmed, and underwhelmed. We look at our lives, relationships, and world, and wonder: Wasn't it all supposed to be more beautiful than this? We quickly silence that question, telling ourselves to be grateful. We hide our simmering discontent--even from ourselves. Until we reach our boiling point. Four years ago, Glennon Doyle--bestselling Oprah-endorsed author, renowned activist and humanitarian, wife and mother of three--was speaking at a conference when a woman entered the room. Glennon looked at her and fell instantly in love. Three words flooded her mind: There She Is. At first, Glennon assumed these words came to her from on high. Soon she realized that they came to her from within. Glennon was finally hearing her own voice--the voice that had been silenced by decades of cultural conditioning, numbing addictions, and institutional allegiances. This was the voice of the girl Glennon had been before the world told her who to be. She vowed to never again abandon herself. She decided to build a life of her own--one based on her individual desire, intuition, and imagination. She would reclaim her true, untamed self. Soulful and uproarious, forceful and tender, Untamed is both a memoir and a galvanizing wake-up call. It offers a piercing, electrifying examination of the restrictive expectations women are issued from birth; shows how hustling to meet those expectations leaves women feeling dissatisfied and lost; and reveals that when we quit abandoning ourselves and instead abandon the world's expectations of us, we become women who can finally look at our lives and recognize: There She Is. Untamed shows us how to be brave. As Glennon insists: The braver we are, the luckier we get"--